Anterior mediastinal solitary fibrous tumor resection by da Vinci® Surgical System in obese patient. (2017) - Amore, Dario; Rispoli, Marco; Cicalese, Marcellino; De Rosa, Ilaria; Rossi, Giuseppe; Corcione, Antonio; Buono, Salvatore; Curcio, Carlo
Highlights: Obese patient are at higher risk for deep sternal wound infection. Robotic-assisted thoracoscopic surgery with da Vinci ® Surgical System is an interesting option. Severe obesity (BMI: 34.3) is not an absolute contraindication to Robotic-assisted thoracoscopic surgery. Abstract: Introduction: Solitary fibrous tumors are uncommon soft tissue tumors initially reported only in the pleura but, in recent years, they have been described at many extra pleural sites, such as mediastinum. The treatment of choice is the extensive surgical resection that is curative for most benign lesions. Presentation of the case: We present the case of solitary fibrous tumor of the anterior mediastinum in obese patient (BMI: 34.3) undergoing complete surgical resection by robotic-assisted thoracoscopic surgery with da Vinci ® Surgical System. Discussion/conclusion: Robotic-assisted thoracoscopic surgery with da Vinci ® Surgical System is an interesting option for obese patient, at higher risk for deep sternal wound infection.